Análise da viabilidade técnica e econômica para concessão de rodovia : estudo de caso aplicado ao pavimento do trecho da RS 324 - Lótici, Raphael Marosin (2010)
The present study aims at evaluating the technical and economic feasibility of deploying a highway toll concession on RS 324 Road in between the towns of Casca and Passo Fundo, so that the highway may have satisfactory levels of comfort and safety for its users. For that the current capacity of the highway was determined and the project was evaluated economically in a deterministic and probabilistic manner. To facilitate understanding on the matter the following topics were addressed theoretically: the types of funding, the social cost of accidents, the public-private partnerships, concessions - especially those in Sao Paulo and Parana and more comprehensively, the concessions in Rio Grande do Sul. In order to develop the case study a survey of the current situation of the road was performed, through an observation of the stretch in analyzes, so that it was possible to check the actual need of improvement. Documents provided by DAER/RS and the company in charge of CREMA were also analyzed in order to accomplish the financial survey of the necessary investments for the improving the conditions of the route. The charts set up for performing the simulations used the toll fees of R$ 2.00, R$ 2.50, R$ 3.00 and R$ 3.50, with a 25-year-term investment. It was also possible to figure out the return fee and the current net fare on the investment made. From this study we have concluded that the setting up of a toll charging point on RS 324 Road in between the cities of Casca and Passo Fundo is feasible, both technically and economically, generating feedback upon the investment whatever the fee is